The Nanos gradient in Drosophila embryos is generated by translational regulation. - Dahanukar, A.; Wharton, R.P. (Genes & Development, 1996)
Abdominal segmentation in the Drosophila embryo is governed by a gradient of Nanos (Nos) emanating from the posterior pole. This gradient is derived from translation of the nos mRNA that is localized in the pole plasm; in contrast, unlocalized nos mRNA is translationally repressed. Here we define the essential signals in the 3' untranslated region (UTR) of nos mRNA. Deletion of a 184-nucleotide translational control element (TCE) from the 3' UTR leads to the derepression of nos mRNA in the bulk cytoplasm and the development of lethal anterior defects. Furthermore, a minimal mRNA containing essentially only the TCE in its 3' UTR rescues nos- embryos to adulthood. The TCE is also sufficient to confer on maternal torso mRNA all three aspects of nos mRNA regulation: translational repression in the bulk cytoplasm, localization to the pole plasm, and translational activation at the posterior pole. These three phenomena are coupled intimately, as mutations in a pair of CUGGC pentamers within the TCE simultaneously abrogate all three regulatory events. This coupling suggests a model in which the polarized distribution of nos protein is generated primarily by translational control and that nos mRNA localization is a byproduct of this regulation, at least in part.